Phosphorus availability in soil amended with biochar from rice rusk and cattle manure and cultivated with common bean - William Gleidson Alves Torres; Fernando Colen; Sugandha Dogra Pandey; Leidivan Almeida Frazão; Regynaldo Arruda Sampaio; Luiz Arnaldo Fernandes (Ciência e Agrotecnologia, 2020)
ABSTRACT The soils of the Brazilian Savanna are generally acidic and have low availability of nutrients, so the use of alternative inputs to improve their fertility should be investigated. The objectives of this study were to evaluate the potential of biochars from rice husk (BHR) and from bovine manure (BCM) in increasing phosphorus availability and their effects on soil chemical properties and in common beans plants. The experiments were carried out in a completely randomized design, in a 4x2+3 factorial scheme with four replicates. The treatments were four biochar doses (1, 2, 3 and 4% m/v), two biochars (BRH and BCM) and three additional treatments (C1, no liming and no fertilization; C2, addition of Ca and Mg carbonate and NPK fertilizers and; C3, addition of Ca and Mg silicate and NK fertilizers). In the highest doses of BRH there was an increase of 2.7, 5.3 and 2.5 times in the P content extracted by Mehlich 1 and quantified by colorimentria, by Mehlich 1 and quantified by spectroscopy and by ion exchange resin and quantified by spectroscopy, respectively. For the highest doses of BCM, the increases in P content were 51.3, 289.2 and 88.4 times greater than in C1, respectively, according to the methods described for BRH. The biochars increased soil pH, CEC, nutrient content and the growth of bean plants compared to C1, especially BCM. However, the production of dry matter was significantly lower than that obtained in C2.